Antimicrobial Pharmacotherapy of Community-acquired Pneumonia in Liver Cirrhosis Patients: Accent on the Antibiotic Resistance Risk Stratification - Natalia Kobelevskaya (Journal of Global Pharma Technology, 2016)
There is a proliferation of bacteria that are resistant to many drugs. This has created the need to: identify risk factors for the acquisition of resistant pathogens; stratify patients infected with pathogens. Such pathogens should be considered when choosing the starting antimicrobial therapy for pneumonia associated with cirrhosis. Therefore, the aim of the work is to study the profile of antimicrobial resistance of community-acquired pneumonia (CAP) pathogens that are detected in patients with cirrhosis. While stratifying patients with the risk of infection by pathogens. A retrospective analysis was carried out of 216 patients who were hospitalized in a multidisciplinary hospital in 2016-2018 with CAP. The patients were with a positive result of a respiratory bacterial culture sampling. As a result, the most common microorganisms in patients with CAP and cirrhosis of the liver of alcoholic etiology were E. coli (34.6%), St.aureus (26.9%) and Klebsiella pneumoniae (23.1%). In patients with cirrhosis of the liver of mixed alcohol-viral etiology, the following microorganisms prevailed: St.aureus (36.1%), E.coli (31.2%) and Klebsiella pneumoniae (22.9%). After analyzing all the results, the authors came to the conclusion that the microorganisms (that cause CAP in patients with cirrhosis) differ depending on the etiology of cirrhosis and are mostly gram-negative (K.pneumoniae and E.coli). Besides, S.aureus appears frequency. In general, causative agents of CAP with multidrug resistance in patients with cirrhosis are detected in 28.5% of patients: 24.6% MDR and 3.96% XDR.Keywords: Pneumonia; Antimicrobial therapy; Antibiotic resistance; Risk stratification.